PENGARUH KONTEN DAN KOMENTAR DALAM PROGRAM INTERTASTE KANAL YOUTUBE BINUS TV TERHADAP PENGETAHUAN KULINER (Studi Kasus pada Mahasiswa Hotel Management Binus University Angkatan Tahun 2014) - William Grinaldi (Universitas Mercu Buana, 2019)
Intertaste is a culinary program in the YouTube channel of BINUS TV to increase the culinary knowledge of its audience. This culinary feature is intended to give references about restaurants with simple, elegant yet dynamic style. In the efforts to increase the knowledge of Hotel Management students of BINUS University, the content and comments on Intertaste could contribute influences. The purpose of this research is to detect influences of content and comments for culinary knowledge of Hotel Management students of BINUS University year 2014. The type of this research is explanative research. The sampling technique used is sensus, whereas the population for this research is used as samples. The data is obtained through the samples by spreading questionnaire with experiment method. The data analysis method used in this research is Mann-Whitney test. The result of the data analysis shows significant influences of content and comments of Intertaste to culinary influences of Hotel Management students of BINUS University year 2014. Keywords: content, comments, culinary, feature, knowledge